“Physics Club” program to strengthen high school students’ physics identity - Fitriyana Fitriyana; Nuril Munfaridah; Nandang Mufti; Sidik Al Kahfi (Universitas PGRI Kanjuruhan Malang, 2025)
Students often struggle to identify and position themselves in physics class which is known as the conceptualization of physics identity. One of the contributing factors is the limited learning environment that fosters engagement and a sense of belonging in physics. This study aims to develop, validate, and test the practicality of physics learning tools in a non-formal context, specifically through a physics club. The research employs the Research and Development (R&D) design with the 4D model (Define, Design, Develop, and Disseminate). The instruments were validity and practicality questionnaires. The content validity was assessed by two experts: one physics lecturer and one physics teacher. In addition, the practicality testing involved one physics teacher and 36 students from Laboratory Senior High School UM (Universitas Negeri Malang). Data were analyzed through descriptive statistic by presenting the percentage of the validity and the aspect of practicality. The developed products include a physics club program book, a physics club activity module, and a physics club material book. The validity results showed that the program content achieved 94% (highly valid), the media and material validity of the physics club activity module scored 81% and 89% respectively (highly valid), and the media and material validity of the physics club material book scored 89% and 91% (highly valid). Practicality tests by teachers and students yielded scores of 97% (highly practical) and 77% (practical), respectively. Based on these results, the physics club learning tools are declared valid and practical for use in order to strengthen students’ physics identity.